Data Industrialization: Between Datafication Commodification, and Digital Infrastructure - Nur, Muhammad (UI Scholars Hub, 2022)
Data is a new oil because in the development of industry and communication technology, digital data can be an important thing that can be produced, distributed, and consumed, or commodified. Every digital data can be obtained from every side of everyday human life so that datafication becomes something commonplace today. On the other hand, the role of digital infrastructure both physical and non-physical as supporting the operation of the internet and the development of industry and communication technology and Data Industrialization cannot be denied. Even the DC/server is used to gain profit for the company itself. This article tries to link datafication, commodification, and the role of digital infrastructure in the process. This article uses a qualitative approach with a systematic review and meta-analysis methods (Crowther, Lim, & Crowther, 2010) which was accompanied by interviews with several relevant informants (Alshenqeeti, 2014) to elaborate related concepts. In this article, I argue that in the digital age, every side of human life can become a digital data which then becomes a digital commodity so that the process of datafication and commodification always appears in every digital data. However, the important role of digital infrastructure both physical non-physical is very important.